The EFFEKTIVITAS PENERAPAN INOVASI METODE FIELD STUDY DENGAN REAL TIME REPORT BERBANTU MIND MAPPING PADA MATERI EKOSISTEM TERHADAP HASIL BELAJAR MAHASISWA CALON GURU IPA - Geterudis Kerans (Jurnal Penelitian Pendidikan IPA, 2022)
Effectiveness generally refers to how far a predetermined goal can be achieved. In order for the goal to be achieved, we must be able to provide the right innovation in a learning process. Learning innovation itself is an interaction between a complex set of practices, methods and designs that are part of the efforts made in higher education to improve the quality of teaching and learning. In this study, researchers applied the Real Time Report innovation to the implementation of the Mind Mapping-assisted Field Study. The aims of this method innovation are; Through Real Time Report Innovation in Field Study, students can report their observations directly and get input at the same time so that the process in the field is more focused. Through Mind Mapping, students can connect the images from the field study with the concepts they have correctly. Furthermore, knowing the effectiveness of the application of the method innovation that is applied to the learning outcomes of prospective teacher students. This study uses quasi-experimental research with one group pretest-posttest design. The results show that the application of the Field Study method with innovation in the form of Real time reports assisted by Mind Mapping is effective in teaching Ecosystems